OWNERSHIP RELATIONS AND THE RIGHT TO WATER IN THE EPOCH OF MASS MIGRATIONS - Nikolić, Dušan; Midorović, Sloboda (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
For long time in the past water had been treated as common goods which was supposed to be equally available to all members of the social community. However, throughout the time, circumstances have changed. The emergence and incremental strengthening of an individual ownership have contributed to the transformation of social relations being established with regard to the use of water resources. Owners of immovable property immediately connected to the sources, are, pursuant to the principle of priority, entitled to use the water for their needs and those of their households (prior tempore, potior iure). According to the traditional view, the neighbours were obliged to restrain from the use of water, up until the property owner met his needs, within the limits of the so called regular use. Following the same logic, a privileged owner of the immovable property could also demand from all other persons not to interfere with his use of water resources (ius excludendi tertii). Namely, entitlement to use water was of an accessory nature and it belonged to the corpus of ownership right, which could, as an absolute right, be enforced against anybody (erga omnes). Later on an independent and transferable right to use water resources was established and its holders could become a state, a local community, a private legal and natural person, regardless of the ownership right over an immovable property connected to the water resource. Meanwhile the understanding of the right of ownership has substantially changed. It is no longer considered an absolute in its original sense. Constitutions of some countries and decisions of the highest national and supranational courts stipulate that the ownership has a social function and that it may be limited in the public interest. Likewise, an entitlement to use water resources may be restricted in the interest of social community, and as the practice of some countries testifies, also in the interest of other natural and legal persons. This view, inter alia, is supported by different forms of public-private partnerships. The right of an immovable property owner to use the water resources could additionally be restricted by recognising the universal human right to water. Connected therewith, the legal theory abounds with dilemmas. The most prominent is the one concerning the existence of such universal human right. Some authors argue that it does not exist, but that it has been in the state of an emerging right. Other writers contend that it is implicitly contained, id est, derived from the exiting human rights, whereas some take a stand that it is a sui generis right. The paper offers a comprehensive analyses of the documents adopted by the United Nations and the Council of Europe, jurisprudence of the European Court of Human Rights along with the regulation of the Republic of Serbia on that matter. Introducing the universal human right to water has a special significance in the present time. There are two main reasons for that. The first one presents the possibility of horizontal application of human rights in civil law relations (constitutionalisation), which may bring to the narrowing of the ownership right in the interest of other persons. The second one being the mass migrations triggered by climate change, global warming and the water scarcity. In such circumstances an adequate legal policy shall be identified, based on an all-encompassing scientific research, followed by adopting the corresponding regulation.